A Meta-analysis on the sensitivity of Philippine Mariculture Species to Acute Ammonia and Hydrogen Sulfide exposure - Despi, Janemma Marie B.; Silapan, Judith R. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Aquatic organisms are highly sensitive to biological byproducts such as ammonia and hydrogen sulfide; hence, maintaining high survival rates remains a challenge in Philippine aquaculture systems. This study aimed to assess the acute toxicity of the unionized ammonia and hydrogen sulfide on selected Philippine mariculture species. Ammonia and hydrogen sulfide toxicity data were obtained from online journal databases and the analyses of raw data accessed from the ecotoxicological database repository of Silapan (2006). Using the 48-hr and 96-hr LC50 data integrated from 10 studies, multiple regression analyses were performed to determine the sensitivity of species to unionized ammonia and hydrogen sulfide in relation to water salinity and DO. GMAVs, SSD models, and HC5 values were generated to compare the sensitivity of species. Lastly, PNEC values were calculated to determine the levels of unionized ammonia and hydrogen sulfide that are projected to protect Philippine mariculture species. This study provides site-specific information on the factors affecting species sensitivity and on the differential sensitivity of invertebrates and vertebrates in Philippine mariculture. Results showed that decreased water salinity and increased DO levels jointly increased the sensitivity of species to both toxicants. The ranked GMAVs showed that bivalves were most tolerant to both toxicants while other marine invertebrates were more sensitive than vertebrates. The HC5 values of 43.08 NH3-N μg L-1 and 12.95 H2S μg L-1 suggest the overall lower tolerance and greater sensitivity of species to hydrogen sulfide than to ammonia. Lastly, the PNEC values of 21.54 NH3-N μg L-1 and 6.47 H2S μg L-1 are the levels of toxicants that Philippine mariculture species are expected to tolerate and not experience acute toxic effects. These PNEC values, being the acute WQC, can serve as the basis for the acceptable levels of unionized ammonia and hydrogen sulfide that would provide short-term protection of Philippine mariculture species.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. June 2022.